Development and application of a soil-based infiltration model - Lim, Wee Han. (2009)
The aim of this study is to develop a conceptual infiltration model with parameters that can be related to the physical properties of a soil, and to develop possible applications for it. The shortcomings of an existing physically meaningful conceptual infiltration model were identified and improved with the aid of a numerical infiltration model. The Green and Ampt infiltration equation coupled to a conceptual tank model was used to overcome the identified shortcomings. Four deficiencies were identified in the existing conceptual infiltration model. They are related to the definition of the tank depth, the time-to-ponding, the percolation flow and the infiltration capacity equations. The deficient equations have been replaced with more physically-based ones in the improved conceptual infiltration model.